Kar tresla se je od lepote folklorne pripovedi iz Selške doline - Benedik, Breda (Založba ZRC, ZRC SAZU, 2017)
Book contains 551 thought-provoking folk tales from the Selca valley, both from the valley towns by the Sora of Selca as well as from the hills. The tales are divided into eleven chapters: fairytales, myths, supersititious, scary, descriptive, legends, historical, ethnological, social, ancedotes and funny stories. They largely follow the spoken language and are written in the Selca dialect, with the exception of the few folk tales where this was not possible. The folk tales from the Zgornja and Spodnja Sorica, Zgornje and Spodnje Danje and Zabrdo still contains words or phrases that were used in the 13th century when the Germans populated the land--From the English summary
Keywords: Mundart; Volksliteratur; Slowenisch; Oberkrain; Selca -- Škofja Loka; Tales / Slovenia; Legends / Slovenia; Folklore / Slovenia